Novel substituted oxadiazole - piperazine derivatives as potential MAO inhibitors: Design, synthesis, in vitro and in silico studies - Uslu, Harun; Saglik, Begum Nurpelin; Osmaniye, Derya; Benkli, Kadriye (Marmara Univ, 2022)
Recent studies have shown that there are many piperazine and oxadiazole derivatives with MAO-A and/or MAO-B inhibitory activity. For this reason in our recent study, a new compound series of oxadiazole - piperazine derivatives (4a-e) were designed, synthesized, characterized and screened their hMAOs inhibitory activities. When the in silico studies were examined, it was seen that the pharmacokinetic properties and interactions with the receptor of synthesized compounds were suitable. Compound 4e, with a NO2 group on the 4-position of the phenyl ring, found showing significant MAO-A inhibitory activity. Compound 4e, was the most effective agent against MAO-A enzyme with IC50 value of 0.116 +/- 0.004 mu M. The newly synthesized oxadiazole - piperazine derivatives appears to be supported studies to design MAO inhibitors to obtain more suitable drugs, against diseases such as depression and anxiety due to MAO-A.
Keywords: hMAOs inhibition; oxadiazole; piperazine; ADME; molecular docking